2012
DOI: 10.1177/1352458512451944
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of driving in individuals with relapsing–remitting multiple sclerosis

Abstract: Participants' on-road performance was more accurately predicted by the model identified in this study than using only performance on the SDSA test battery. The five psychometric/off-road tests should be used as a screening battery, after which a follow-up road test should be conducted to finally decide the fitness to drive of individuals with relapsing-remitting MS. Future studies are needed to confirm and validate the findings in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
79
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(90 citation statements)
references
References 37 publications
8
79
3
Order By: Relevance
“…This finding can be attributed to the differences in the cohort of individuals with MS in this study and the previous one (Akinwuntan et al, 2013a). In this study, individuals with all types of MS and with moderate disability in one functional system; or mild disability in three or four functional systems, though fully ambulatory (EDSS = 3) to those unable to walk beyond 5 meters even with aid (EDSS = 7) were included.…”
Section: Discussionmentioning
confidence: 86%
See 4 more Smart Citations
“…This finding can be attributed to the differences in the cohort of individuals with MS in this study and the previous one (Akinwuntan et al, 2013a). In this study, individuals with all types of MS and with moderate disability in one functional system; or mild disability in three or four functional systems, though fully ambulatory (EDSS = 3) to those unable to walk beyond 5 meters even with aid (EDSS = 7) were included.…”
Section: Discussionmentioning
confidence: 86%
“…In this preliminary report, we sought to validate the predictive accuracy of the five cognitive tests identified in a previous study (Akinwuntan et al, 2013a) as predictive of the driving performance of individuals with MS in a new cohort of individuals with MS. Our findings showed that the battery of five cognitive tests, including the Stroop Color test, the Direction, Compass, and Road Sign Recognition tests of the SDSA battery, and the Speed of Processing subtest of the UFOV test, appears to be a very good predictor of the on-road driving ability of individuals with MS. The three primary cognitive domains assessed by the five tests are some of the most important cognitive skills required for safe driving.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations